2005
DOI: 10.1007/s10886-005-6082-7
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Sexual Behavior and Pheromone Titers of Two Closely Related Moth Species Autographa gamma and Cornutiplusia circumflexa1

Abstract: Two closely related plusiinae moths, Autographa gamma Linnaeus and Cornutiplusia circumflexa Linnaeus, are sympatric in Israel. Both species use identical sex pheromone components but in different ratios, and do not attempt to mate with each other. In addition to the effective reproductive separation by their sex pheromones, the sexual behavior of both species was compared to determine whether the lack of selection pressure might create additional barriers to cross-attraction and cross-mating. We found the gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Others report the proportion of females calling (Hendrikse 1979) or how early calling begins each night (Delisle and McNeil 1987;Kou and Chow 1987;Delisle 1992). Several studies report changes in calling bout number and bout length (Howlader and Gerber 1986;Jacas and Peña 2002;Mazor and Dunkelblum 2005;Ming et al 2007), with calling bout defined as a period of time over which a female is observed in the characteristic position of raising her abdomen and periodically everting her ovipositor.…”
Section: Empirical Evidence On Female Signaling Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…Others report the proportion of females calling (Hendrikse 1979) or how early calling begins each night (Delisle and McNeil 1987;Kou and Chow 1987;Delisle 1992). Several studies report changes in calling bout number and bout length (Howlader and Gerber 1986;Jacas and Peña 2002;Mazor and Dunkelblum 2005;Ming et al 2007), with calling bout defined as a period of time over which a female is observed in the characteristic position of raising her abdomen and periodically everting her ovipositor.…”
Section: Empirical Evidence On Female Signaling Effortmentioning
confidence: 99%
“…Increasing calling rate with age may be a behavioral strategy for older females to cope with a physiologically driven decline in pheromone production (Webster and Cardé 1982;Delisle and Royer 1994;Mazor and Dunkelblum 2005). Unfortunately, data for both traits together exist for only 12 species in 13 studies (table 1).…”
Section: Interpretation Of Empirical and Theoretical Evidencementioning
confidence: 99%
“…Some other species showed a similar synchronous relationship between calling and the amount of pheromone with the change of age or time, such as Spodoptera exigua, Autographa gamma, Cornutiplusia circumflexa, Isoceras sibirica, and Agrotis ipsilon (Dong & Du 2001;Mazor & Dunkelblum 2005;Xiang et al 2010;Liu et al 2013). This coincidence between pheromone production and female calling indicates a common regulatory mechanism for both processes (Gemeno & Haynes 2000).…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, the advanced onset time of calling with increase in age in Lepidopteran species is an adaptation that permits older females to increase their chances of mating before younger females start calling (Delisle & Royer 1994). Older females would be at a disadvantage compared to younger ones if they did not extend their calling period (Delisle & Royer 1994;Mazor & Dunkelblum 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are typically species-specific peaks in pheromone release during the light:dark cycle; however, exact onset and duration is modulated by age and abiotic factors (Dreisig, 1986;Delisle and McNiel, 1987;McNeil, 1991;Rosén, 2002;Silvegren et al, 2005;Mazor and Dunkelblum, 2005). Some have reported that aphids release sex pheromone only during the photophase (Marsh, 1972;Eisenbach and Mittler, 1980;Eisenbach and Mittler, 1987) and in sympatric situations there is some evidence that pheromone release during the photophase is divided according to the aphid sub-species (Guldemond and Dixon, 1994;Thieme and Dixon, 1996).…”
Section: Introductionmentioning
confidence: 99%